Microbial quality of mung bean (Vigna Radiata, L. Wilczek) sprouts from selected wet markets of Quezon City, Philippines - Lopez, Maria Gracia Angelica Ancla (2005)
This study was undertaken to determine the microbial quality of mung bean sprouts vended in selected wet markets in Quezon City, Philippines. Documentations of sprout production, handling, transportation and vending practices of sprout vendors and producers were done. The microbial quality parameters included total plate count (TPC), yeast and mold counts (YMC), lactic acid bacteria (LAB) counts, total coliform (TCC), generic E.coli counts (GEC) and Salmonella spp. Results showed that mung bean sprouts from the different testing sites had TPCs in the range of 9.29-10.88 log10 cfu g^-1, YMC's of 4.58-5.31 log10 cfu g^-1, LAB counts of 9.14-10.70 log10cfug^-1, TCCs of 6.18-7.25 log10cfug^-1 and GEC of <4.00-4.30 log 10cfug^-1. Salmonella spp. was detected in all the samples. The thermal inactivation of Salmonella typhimarium E1366 in mung bean sprouts was alo established. The established values of S. typhimarium E1366 in cooked mung bean sprouts were 0.28, 0.28 and 0.12 min at 60, 70 and 90°C, respectively.